Análise de fluxo de materiais e energia para um processo produtivo de porcelanato com contabilidade de gases de efeito estufa - Brito, Alexandre Magno Vieira Gonçalves de (2022)
The environment and sustainable development are currently seen as opportunities, as possibilities for growth and efficiency improvement. In this way, it is still possible to establish sustainable growth in Brazilian companies by implementing policies and creating awareness among entrepreneurs and society. The objective of this study is to measure the environmental impact associated with a porcelain tile production line. Application of the Material and Energy Flow Analysis (MEFA) provides the raw materials and energy flows associated with the ceramic production process. The production line includes grinding, atomizing, forming, drying, enameling, sintering and finishing. All equipment consume electricity from the grid, except atomization that uses coke. The Life Cycle Assessment (LCA) methodology is applied to quantify the greenhouse gas (GHG) emissions associated with this production line. MEFA revealed that the monthly losses of the production line are 1,186,600 kg of material, with a consumption of 201.896 kWh electricity and 29.754 kWh coke. Considering the representative processes associated with the consumption of electricity from the Brazilian electric grid and coke, the GHG emissions are 0.268 kg CO2-eq/kWh and 0.558 kg CO2-eq/kWh, respectively. In this case, the monthly GHG emissions of the production process are 70,711 kg CO2-eq, equivalent to 70.71 kg CO2-q/ t porcelain tile. Even the partial introduction of solar photovoltaic electricity was beneficial to reduce GHG emissions, as 9,027 kg CO2-eq/month can be avoided for every 20% electricity replaced (using photovoltaic panels instead of the electricity grid).